Analysis of Building to Enhance The Sustainability - Deshbhushan Patil, S K Sekar (International Journal of Advanced Science and Technology, 2020)
The reason for this exploration is to add to a superior understanding of the idea of green structure evaluation instrument and its job for accomplishing sustainable advancement through building up a compelling green structure rating framework. Green building is nothing but the structure constructed considering the environment responsibility, resource efficient throughout life cycle of the building, which has minimal impact on the environment. Green building deals with the all the phases of design, material selection, and construction which includes the analysis of energy. In India near about 1 billion square foot building area certified as green building from Leadership in Energy and Environmental Design(LEED), through the concept of the green building reduces the energy consumption of the building by 40% as compared to other building which majorly effects on the running operational cost of the building[3].This paper deals with the current contemplations on supportable development especially with respect to the fundamental components of practical development and manageability criteria and markers. For the analysis of the practical building was considered an institutional building. According to the rating framework for the green building this building goes under the platinum rating.